Shakespeare and his stage approaches to Hamlet - Seltzer, Daniel; Mantell, Harold; Films for the Humanities (Firm). (Princeton, N.J. Films for the Humanities, 1975)
A young actor's attempts to master the role of Hamlet are intercut with footage of the four greatest Hamlets of this century: John Barrymore, Lawrence Olivier, John Gielgud and Nicol Williamson.
VHS.
"FFH121."
Narrated by John Gielguld ; edited by Carlo Arcamone.
Stephen Tate as Hamlet, Lesley Duff as Ophelia ; Hamlet interpreted by Laurence Olivier, John Gielgud, Nicol Williamson, John Barrymore.
Keywords: Shakespeare, William -- 1564-1616.; Shakespeare, William -- 1564-1616 -- Dramatic production; Theater -- History. -- England